Answer:
y = -1/3x + 6
![(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/54kd5otoayi7fslqp2ejx77tdkhh8ubevy.png)
Explanation:
First, change the original equation to slope intercept form:
y + 4 = 3x
y = 3x - 4
Now, find the slope of the perpendicular line. It will be the opposite reciprocal:
The opposite reciprocal of 3 is -1/3.
Next, plug this into the slope intercept equation along with the given point, so we can solve for b:
y = mx + b
6 = -1/3(2) + b
6 = -2/3 + b
6.67 = b
So, the equation will be y = -1/3x + 6
![(2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/54kd5otoayi7fslqp2ejx77tdkhh8ubevy.png)